Privacy-aware deep learning for gender detection - Lee, Craigdon Zhi Jie (Nanyang Technological University, 2021)
With the recent advancements made in deep learning, it is clear that deep learning has become the most promising approach in artificial intelligence to tackle complex problems. Deep learning has shown its prowess in being able to learn large amounts of features due to its substantial learning capacity.